Country Insurance - Levy Yeyati, Eduardo (IMF Working Papers; Working Paper, 2004)
In this paper, we examine how the presence of country insurance schemes affects policymakers' incentives to undertake reforms. Such schemes (especially when made contingent on negative external shocks) are more likely to foster than to delay reform in crisis-prone volatile economies. The consequences of country insurance, however, hinge on the nature of the reforms being considered: "buffering" reforms, aimed at mitigating the cost of crises, could be partially substituted for, and ultimately discouraged by, insurance. By contrast, "enhancing" reforms that pay off more generously in the absence of a crisis are likely to be promoted.